A high-performance pressureless sintered silicon carbide slip casting preparation method

By regulating the components and modification treatment of silicon carbide slurry in the grouting molding-pressure-free sintering process, silicon carbide ceramics with high solid phase content and low viscosity were prepared, and the poor slurry stability in the existing process was solved. Problem, the preparation of high-performance silicon carbide ceramics has been realized.

CN118619679BActive Publication Date: 2024-12-20NANTONG SANZER PRECISION CERAMICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411087328.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-20
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The existing grouting molding-pressure-free sintering process is difficult to prepare silicon carbide slurries with high solid phase content, low viscosity and good stability, resulting in insufficient performance of silicon carbide ceramic products.

Method used

By mixing the sintering aid, pH adjuster, dispersant, binder and degluing agent with modified silicon carbide powder in deionized water, the stirring rate is gradually increased after even stirring, and defoaming is carried out, combining gypsum mold mold forming and solidification The phase pressure-free sintering process regulates the solid content and viscosity of the slurry to prepare silicon carbide ceramic products with high solid phase content and low viscosity.

Benefits of technology

The preparation of silicon carbide slurry with high solid phase content, low viscosity and good stability was achieved. Through grouting molding and pressure-free sintering processes, high-performance silicon carbide ceramic products were obtained, with good density, hardness and thermal conductivity. Rate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a high-performance pressureless sintered silicon carbide grouting molding preparation method, which relates to the field of ceramic technology, and includes the following steps: mixing and dispersing a sintering aid, a pH regulator, a dispersant, a binder and a debonding agent into deionized water, stirring evenly to obtain a premix; adding modified silicon carbide powder to the premix under stirring conditions, and gradually increasing the stirring rate to obtain a slurry; degassing the slurry, pouring the degassed slurry into a gypsum mold for molding, pouring out the excess slurry, and demolding after the initial drying and shrinkage of the green body to obtain a green body; heating and drying the green body, repairing the dried green body, placing the treated green body into a sintering furnace for sintering according to the sintering system to obtain a silicon carbide ceramic product. The present application has the effect of increasing the solid content of the ceramic slurry and reducing the viscosity of the ceramic slurry, and the prepared product has high density, high hardness and good thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramic technology, and in particular to a method for preparing high-performance pressureless sintered silicon carbide by slip casting. Background Art

[0002] Silicon carbide (SiC) ceramics not only have excellent room temperature mechanical properties, such as high flexural strength, excellent oxidation resistance, good corrosion resistance, high wear resistance and low friction coefficient, but also have the best high temperature mechanical properties (strength, creep resistance, etc.) among known ceramic materials. Its products are widely used in aerospace, aviation, national defense, automobile, chemical industry, nuclear energy and other fields.

[0003] Among the sintering processes commonly used in silicon carbide production, pressureless sintering is the most basic sintering method. The relative density of the resulting SiC ceramics is greater than 95% of the theoretical density, and the grains are fine. It has good high-temperature mechanical properties and is suitable for firing objects of different shapes and sizes, and the temperature is also easy to control. There are two main molding methods for silicon carbide high-temperature mechanical properties ceramics: pressure and injection molding. The organic reagents added to the grouting molding are mainly non-toxic or low-toxic dispersants, and the grouting molding process is simple to operate and has low cost. The grouting molding-pressureless sintering process uses a gypsum mold to control the shape of the product, and can prepare products of various shapes. No dust pollution is generated during the molding process, and water is used as the medium, which does not cause any harm to the human body.

[0004] In the slip casting process, the ceramic slurry used is a high solid phase, low viscosity silicon carbide slurry. Surface treatment of SiC powder particles and selection of suitable SiC powder dispersants to improve the dispersibility, fluidity and stability of solid particles in the slurry are the key to preparing high solid phase, low viscosity silicon carbide slurry. In order to ensure the high temperature performance of silicon carbide ceramics and avoid the formation of glass phase at the grain boundary, solid phase pressureless sintering is usually used. The smaller the radius of the powder particles and the larger the specific surface area, the more conducive to the lattice diffusion of C and Si. Therefore, there are further requirements for the particle size of the raw materials, and pressureless sintering can usually be achieved below 1μm. However, it is difficult to adjust the slurry of ultrafine raw materials. At present, there are few reports on slip casting-pressureless sintering process. Therefore, it is necessary to prepare a slurry with high solid content, low viscosity, good stability, suspension and suitable thixotropy, and prepare products with good performance through slip casting and solid phase pressureless sintering. Summary of the invention

[0005] In order to increase the solid content of silicon carbide ceramic slurry and reduce the viscosity of the slurry, the present application provides a high-performance pressureless sintered silicon carbide slip casting molding preparation method.

[0006] The present application provides a high-performance pressureless sintered silicon carbide slip casting preparation method using the following technical solutions:

[0007] A high-performance pressureless sintered silicon carbide slip casting preparation method comprises the following steps:

[0008] The sintering aid, pH regulator, dispersant, binder and debonding agent are mixed and dispersed in deionized water, and stirred evenly to obtain a premixed solution;

[0009] Adding modified silicon carbide powder to the premixed liquid under stirring conditions, and gradually increasing the stirring rate as the amount of modified silicon carbide powder added increases, to obtain a slurry;

[0010] Degassing the slurry to obtain degassing slurry;

[0011] The degassed slurry is poured into a plaster mold for molding, and the excess slurry is poured out. After the green body is initially dried and shrunk, it is demoulded to obtain a green body;

[0012] heating and drying the green body to obtain a dried green body;

[0013] The dried green body is subjected to a trimming treatment, and the treated green body is placed in a sintering furnace for sintering treatment according to a sintering system to obtain a silicon carbide ceramic product.

[0014] By regulating the components of sintering aids, pH regulators, dispersants, binders and debonding agents and modifying silicon carbide powder, a slurry with high solid content, low viscosity, good stability, suspension and suitable thixotropy is obtained; the modified silicon carbide powder has the characteristics of shear thinning, and gradually increasing the stirring rate can reduce the viscosity of the slurry; through slip injection molding and pressureless sintering technology, products with good performance in various shapes can be prepared through simple processes.

[0015] Preferably, the slurry comprises the following components in percentage by weight: 3-7% sintering aid, 2.5-6% pH adjuster, 2-5% dispersant, 2-4% binder, 0.5-2% debonding agent, 15-22% deionized water, and the remainder is modified silicon carbide powder.

[0016] The slurry prepared according to the above composition and percentage has high solid content and low viscosity, is suitable for slip casting process, and has good stability, suspension and suitable thixotropy.

[0017] Preferably, the sintering aid includes carbon black and boron carbide.

[0018] Carbon black is a nanomaterial with high surface area and porosity, which can improve the density and hardness of silicon carbide ceramics; boron carbide can significantly improve the hardness of silicon carbide ceramics, making them more wear-resistant and corrosion-resistant; boron carbide can also improve the thermal conductivity of silicon carbide ceramics, reduce the heat loss of silicon carbide ceramics at high temperatures, and improve the quality and service life of silicon carbide ceramics; by adding carbon black and boron carbide as sintering aids, the two can synergistically improve the density, hardness and thermal conductivity of silicon carbide ceramics, thereby improving the quality and service life of the ceramics.

[0019] Preferably, the pH adjuster comprises tetramethylammonium hydroxide.

[0020] Tetramethylammonium hydroxide can adjust the pH value of the slurry, thereby regulating the rheological properties of the slurry and improving the stability of the slurry; Tetramethylammonium hydroxide can also work synergistically with the dispersant to help the modified silicon carbide powder to be evenly dispersed in the slurry and reduce the occurrence of particle aggregation and precipitation.

[0021] Preferably, the modified silicon carbide powder comprises pretreated silicon carbide ultrafine powder, a silane coupling agent and modified polyacrylamide, and the amount of the silane coupling agent and the modified polyacrylamide accounts for 0.5-1% of the total weight of the slurry.

[0022] The pretreated silicon carbide ultrafine powder is modified by using silane coupling agent and modified polyacrylamide. The silane coupling agent can help the powder to disperse, increase the surface active groups of the pretreated silicon carbide ultrafine powder, and facilitate the grafting reaction of modified polyacrylamide on the powder surface. The modified polyacrylamide can further promote the uniform dispersion of the modified silicon carbide powder in the slurry through modification.

[0023] Preferably, the pretreated silicon carbide ultrafine powder is prepared by the following steps: ultrasonically dispersing the silicon carbide ultrafine powder into a hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, stirring the silicon carbide dispersion to react, centrifuging, washing, and drying to obtain preliminary treated silicon carbide; mixing and dispersing the preliminary treated silicon carbide and glacial acetic acid to obtain a pretreated dispersion, heating the pretreated dispersion to react, centrifuging, washing, and drying to obtain pretreated silicon carbide ultrafine powder.

[0024] The silicon carbide ultrafine powder is initially washed with a dilute hydrochloric acid aqueous solution to remove impurities on the surface of the silicon carbide ultrafine powder and reduce the occurrence of self-aggregation; the initially treated silicon carbide and glacial acetic acid are mixed and heated to react. Under heating conditions, the acetic acid molecules are stably adsorbed on the surface of the powder, and the repulsion between the powders is increased through the dual effects of steric hindrance and electrostatic stabilization, thereby reducing agglomeration and facilitating subsequent further modification treatments.

[0025] Preferably, the raw materials for preparing the modified polyacrylamide include dimethyl dioctadecyl ammonium chloride, acrylamide and polyethyleneimine.

[0026] Dimethyldioctadecylammonium chloride is a gemini quaternary ammonium salt with two hydrophobic tail groups and a hydrophilic head group, which can help the modified silicon carbide powder to be well dispersed, reduce the viscosity of the slurry, and improve the uniformity of the slurry; acrylamide and polyethyleneimine can form a three-dimensional interpenetrating network polymer. The interpenetrating polymer is further modified by dimethyldioctadecylammonium chloride to form a steric hindrance and electrostatic stabilization effect, which synergizes with the acetic acid molecules to further improve the dispersibility of the modified silicon carbide powder, increase the solid content of the slurry, and reduce the viscosity, so that the obtained green body has good density, thereby improving the density, hardness and thermal conductivity of the product.

[0027] Preferably, the mass ratio of dimethyldioctadecylammonium chloride, acrylamide and polyethyleneimine is (0.2-0.4):1:0.5.

[0028] The modified silicon carbide powder prepared according to the above mass ratio has good dispersibility, and the prepared slurry has high solid content and low viscosity, which reduces the water content of the green body, increases the density and hardness of the green body, and thus improves the thermal conductivity of the product.

[0029] Preferably, the degassing treatment is a vacuum stirring degassing treatment, and the treatment time is 10-30 minutes.

[0030] The rapid degassing treatment according to the above time saves the time of the aging step, reduces the influence of solvent volatilization on the performance of the ceramic slurry, keeps the slurry in a low viscosity state, facilitates the subsequent formation of the green body, and shortens the production cycle.

[0031] Preferably, the sintering system includes the following contents: a heating rate of 8-12°C / min, keeping at 1150°C, 1330°C, and 1550°C for 0.5-1.5h respectively, and a final sintering temperature of 2150-2250°C, keeping at this temperature for 1.5-2.5h.

[0032] The product obtained according to the above sintering system has good density, hardness and thermal conductivity.

[0033] In summary, the present application includes at least one of the following beneficial technical effects:

[0034] 1. By regulating the components of sintering aids, pH regulators, dispersants, binders and debonding agents and modifying silicon carbide powder, a slurry with high solid content, low viscosity, good stability, suspension and suitable thixotropy is obtained; the modified silicon carbide powder has the characteristics of shear thinning, and gradually increasing the stirring rate can reduce the viscosity of the slurry; through slip injection molding and pressureless sintering technology, products with good performance in various shapes can be prepared through simple processes.

[0035] 2. The silicon carbide ultrafine powder is initially washed with a dilute hydrochloric acid aqueous solution to remove impurities on the surface of the silicon carbide ultrafine powder and reduce the occurrence of self-aggregation; the initially treated silicon carbide and glacial acetic acid are mixed and heated to react. Under heating conditions, the acetic acid molecules are stably adsorbed on the surface of the powder, and the repulsion between the powders is increased through the dual effects of steric hindrance and electrostatic stabilization, reducing agglomeration, and also facilitating subsequent further modification treatments.

[0036] 3. Dimethyldioctadecylammonium chloride can help the modified silicon carbide powder to be well dispersed, reduce the viscosity of the slurry, and improve the uniformity of the slurry; acrylamide and polyethyleneimine can form a three-dimensional interpenetrating network polymer. The interpenetrating polymer is further modified by dimethyldioctadecylammonium chloride to form a steric hindrance and electrostatic stabilization effect, and synergize with the acetic acid molecules to further improve the dispersibility of the modified silicon carbide powder, increase the solid content of the slurry, and reduce the viscosity, so that the obtained green body has a good density, thereby improving the density, hardness and thermal conductivity of the product. DETAILED DESCRIPTION

[0037] The present application discloses a method for preparing high-performance pressureless sintered silicon carbide by slip casting. The prepared product is a silicon carbide heat exchange tube as an example. The raw materials involved in the present application can be obtained commercially. The present application is further described in detail in conjunction with the embodiments below:

[0038] Raw materials description: The dispersants are CE64 and 5088, CE64 was purchased from Qiren Chemical, 5088 was purchased from Wuhan Meiqilin New Materials Co., Ltd., the binder is 94 binder, model DP8810NS, the pH adjuster is tetramethylammonium hydroxide (CAS No.: 75-59-2), the debonding agent is PC75, purchased from Borealis, and the silane coupling agent model is KH-550.

[0039] Example 1

[0040] Preparation of modified silicon carbide powder

[0041] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of a 5% by mass hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, the silicon carbide dispersion was stirred at a speed of 200 rpm and then centrifuged, washed with deionized water and then dried to obtain preliminary treated silicon carbide; the preliminary treated silicon carbide and 110 L of glacial acetic acid were mixed and dispersed to obtain a pretreated dispersion, the pretreated dispersion was heated at 120° C. for 3 hours, cooled and then centrifuged, washed with deionized water and then dried to obtain pretreated silicon carbide ultrafine powder.

[0042] 0.3 kg of silane coupling agent was dispersed in 100 L of xylene, and the mixture was heated at 60° C. and stirred at 200 rpm for 15 min to obtain a silane coupling agent solution. 99.26 kg of pretreated silicon carbide ultrafine powder was added to the silane coupling agent solution under stirring at 200 rpm. The addition was completed within half an hour to obtain a preliminary modified dispersion. The preliminary modified dispersion was reacted in a nitrogen atmosphere at 85° C. for 4 h, and dried at 70° C. for 10 h after centrifugation to obtain a preliminary modified silicon carbide powder.

[0043] The preliminary modified silicon carbide powder prepared above was dispersed in 100 L of deionized water to obtain a preliminary modified dispersion, 0.05 kg of dimethyldioctadecylammonium chloride (CAS No.: 107-64-2), 0.26 kg of acrylamide (CAS No.: 79-06-1) and 0.13 kg of polyethyleneimine (CAS No.: 9002-98-6) were added to the preliminary modified dispersion, and 2 g of methylbisacrylamide was added as a cross-linking agent to obtain a reaction solution, the reaction solution was stirred at 80° C. and 300 rpm for 4 hours, and a solid was obtained after centrifugation. The solid was dried at 100° C. for 8 hours to obtain a modified silicon carbide ultrafine powder.

[0044] Preparation of silicon carbide heat exchange tubes

[0045] 3 kg of sintering aid, 2.5 kg of pH regulator, 2 kg of dispersant, 2 kg of binder and 0.5 kg of debonding agent were mixed and dispersed in 22 L of deionized water, and stirred evenly to obtain a premixed liquid; the mass ratio of carbon black and boron carbide in the above sintering aid was 1:3, and the mass ratio of CE64 and 5088 in the above dispersant was 3:8; 68 kg of modified silicon carbide powder was added to the premixed liquid under stirring at 100 rpm, and the stirring rate was gradually increased to 200 rpm as the amount of modified silicon carbide powder added increased to obtain a slurry; the slurry was subjected to vacuum stirring and degassing treatment for 1 0min to obtain a degassed slurry; pour the degassed slurry into a gypsum mold for molding, pour out the excess slurry, and demould the green body after preliminary drying and shrinkage to obtain a green body; heat and dry the green body to obtain a dried green body; trim the dried green body, put the treated green body into a sintering furnace and sinter it according to the sintering system, the above sintering system is: heating rate of 8℃ / min, keeping warm at 1150℃, 1330℃, 1550℃ for 0.5h respectively, and finally firing at 2150℃ for 1.5h to obtain a silicon carbide ceramic product.

[0046] Example 2

[0047] Preparation of modified silicon carbide powder

[0048] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of a 5% by mass hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, the silicon carbide dispersion was stirred at a speed of 200 rpm and then centrifuged, washed with deionized water and then dried to obtain preliminary treated silicon carbide; the preliminary treated silicon carbide and 110 L of glacial acetic acid were mixed and dispersed to obtain a pretreated dispersion, the pretreated dispersion was heated at 120° C. for 3 hours, cooled and then centrifuged, washed with deionized water and then dried to obtain pretreated silicon carbide ultrafine powder.

[0049] 0.66 kg of silane coupling agent was dispersed in 100 L of xylene, and the mixture was heated at 60° C. and stirred at 200 rpm for 15 min to obtain a silane coupling agent solution. 98.36 kg of pretreated silicon carbide ultrafine powder was added to the silane coupling agent solution under stirring at 200 rpm. The addition was completed within half an hour to obtain a preliminary modified dispersion. The preliminary modified dispersion was reacted in a nitrogen atmosphere at 85° C. for 4 h, and dried at 70° C. for 10 h after centrifugation to obtain a preliminary modified silicon carbide powder.

[0050] The preliminary modified silicon carbide powder prepared above was dispersed in 100 L of deionized water to obtain a preliminary modified dispersion, 0.21 kg of dimethyldioctadecylammonium chloride (CAS No.: 107-64-2), 0.52 kg of acrylamide (CAS No.: 79-06-1) and 0.25 kg of polyethyleneimine (CAS No.: 9002-98-6) were added to the preliminary modified dispersion, and 4 g of methylbisacrylamide was added as a cross-linking agent to obtain a reaction solution, the reaction solution was stirred at 80° C. and 300 rpm for 4 hours, and a solid was obtained after centrifugation. The solid was dried at 100° C. for 8 hours to obtain a modified silicon carbide ultrafine powder.

[0051] Preparation of silicon carbide heat exchange tubes

[0052] 7 kg of sintering aid, 6 kg of pH regulator, 5 kg of dispersant, 4 kg of binder and 2 kg of debonding agent were mixed and dispersed in 15 L of deionized water, and stirred evenly to obtain a premixed liquid; the mass ratio of carbon black and boron carbide in the above sintering aid was 3:5, and the mass ratio of CE64 and 5088 in the above dispersant was 2:3; 61 kg of modified silicon carbide powder was added to the premixed liquid under stirring conditions of 100 rpm, and the stirring rate was gradually increased to 200 rpm as the amount of modified silicon carbide powder added increased to obtain a slurry; the slurry was subjected to vacuum stirring and degassing treatment for 30 min. in, to obtain a deaerated slurry; pour the deaerated slurry into a gypsum mold for molding, pour out the excess slurry, and demould the green body after preliminary drying and shrinkage to obtain a green body; heat and dry the green body to obtain a dried green body; perform green body repair on the dried green body, place the treated green body in a sintering furnace and perform sintering according to a sintering system, wherein the sintering system is as follows: a heating rate of 12°C / min, and heat preservation at 1150°C, 1330°C, and 1550°C for 1.5h respectively, and a final sintering temperature of 2250°C for 2.5h to obtain a silicon carbide ceramic product.

[0053] Example 3

[0054] Preparation of modified silicon carbide powder

[0055] 110 kg of silicon carbide ultrafine powder was ultrasonically dispersed in 110 L of a 5% by mass hydrochloric acid aqueous solution to obtain a silicon carbide dispersion, the silicon carbide dispersion was stirred at a speed of 200 rpm and then centrifuged, washed with deionized water and then dried to obtain preliminary treated silicon carbide; the preliminary treated silicon carbide and 110 L of glacial acetic acid were mixed and dispersed to obtain a pretreated dispersion, the pretreated dispersion was heated at 120° C. for 3 hours, cooled and then centrifuged, washed with deionized water and then dried to obtain pretreated silicon carbide ultrafine powder.

[0056] 0.46 kg of silane coupling agent was dispersed in 100 L of xylene, and the mixture was heated at 60° C. and stirred at 200 rpm for 15 min to obtain a silane coupling agent solution. 98.84 kg of pretreated silicon carbide ultrafine powder was added to the silane coupling agent solution under stirring at 200 rpm. The addition was completed within half an hour to obtain a preliminary modified dispersion. The preliminary modified dispersion was reacted in a nitrogen atmosphere at 85° C. for 4 h, and dried at 70° C. for 10 h after centrifugation to obtain a preliminary modified silicon carbide powder.

[0057] The preliminary modified silicon carbide powder prepared above was dispersed in 100 L of deionized water to obtain a preliminary modified dispersion, 0.12 kg of dimethyldioctadecylammonium chloride (CAS No.: 107-64-2), 0.39 kg of acrylamide (CAS No.: 79-06-1) and 0.19 kg of polyethyleneimine (CAS No.: 9002-98-6) were added to the preliminary modified dispersion, and 4 g of methylbisacrylamide was added as a cross-linking agent to obtain a reaction solution, the reaction solution was stirred at 80° C. and 300 rpm for 4 hours, and a solid was obtained after centrifugation. The solid was dried at 100° C. for 8 hours to obtain a modified silicon carbide ultrafine powder.

[0058] Preparation of silicon carbide heat exchange tubes

[0059] 5 kg of sintering aid, 4.25 kg of pH regulator, 3.5 kg of dispersant, 3 kg of binder and 1.25 kg of debonding agent were mixed and dispersed in 18.5 L of deionized water, and stirred evenly to obtain a premixed liquid; the mass ratio of carbon black and boron carbide in the above sintering aid was 5:11, and the mass ratio of CE64 and 5088 in the above dispersant was 1:2; 64.5 kg of modified silicon carbide powder was added to the premixed liquid under stirring at 100 rpm, and the stirring rate was gradually increased to 200 rpm as the amount of modified silicon carbide powder added increased to obtain a slurry; the slurry was vacuum stirred The degassing treatment is carried out for 30 minutes to obtain a degassing slurry; the degassing slurry is poured into a gypsum mold for molding, and the excess slurry is poured out. After the green body is initially dried and shrunk, it is demoulded to obtain a green body; the green body is heated and dried to obtain a dried green body; the dried green body is trimmed, and the treated green body is placed in a sintering furnace for sintering according to the sintering system. The sintering system is as follows: the heating rate is 10°C / min, and the temperatures are kept at 1150°C, 1330°C, and 1550°C for 1h respectively, and the final firing temperature is 2200°C, which is kept for 2h to obtain a silicon carbide ceramic product.

[0060] Example 4

[0061] Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of dimethyldioctadecylammonium chloride used is 0.04 kg, the amount of acrylamide used is 0.44 kg, and the amount of polyethyleneimine used is 0.22 kg.

[0062] Example 5

[0063] Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of dimethyldioctadecylammonium chloride used is 0.175 kg, the amount of acrylamide used is 0.35 kg, and the amount of polyethyleneimine used is 0.175 kg.

[0064] Example 6

[0065] Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the amount of silane coupling agent and modified polyacrylamide used is 0.2% of the total weight of the slurry.

[0066] Example 7

[0067] Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of silane coupling agent and modified polyacrylamide used is 2% of the total weight of the slurry.

[0068] Example 8

[0069] Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, no silane coupling agent is added when preparing the modified silicon carbide powder, and the remainder is supplemented with modified polyacrylamide.

[0070] Example 9

[0071] Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, no dimethyl dioctadecyl ammonium chloride is added when preparing the modified silicon carbide powder, and the remainder is supplemented with acrylamide.

[0072] Example 10

[0073] Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that polyethyleneimine is not added when preparing the modified silicon carbide powder in Example 10, and the balance is supplemented with acrylamide.

[0074] Embodiment 11

[0075] Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, the pretreated silicon carbide ultrafine powder is replaced by silicon carbide ultrafine powder.

[0076] Example 12

[0077] Example 12 is based on Example 3, and the only difference between Example 12 and Example 3 is that in Example 12, tetramethylammonium hydroxide is replaced by sodium hydroxide.

[0078] Embodiment 13

[0079] Example 13 is based on Example 3, and the only difference between Example 13 and Example 3 is that the vacuum stirring degassing treatment time in Example 13 is 5 minutes.

[0080] Embodiment 14

[0081] Example 14 is based on Example 3. The only difference between Example 14 and Example 3 is that the vacuum stirring degassing treatment time in Example 14 is 45 minutes.

[0082] Comparative Example 1

[0083] Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the modified silicon carbide powder is replaced with ultrafine silicon carbide powder. Performance testing

[0084] (1) Density test: The sample was prepared into a cubic silicon carbide ceramic specimen of 100 mm * 200 mm * 20 mm. The volume density was calculated and recorded based on the volume and mass. The X-ray diffraction pattern of the sample was taken. The theoretical density was calculated based on the lattice constant and crystal structure of the sample. The relative density was calculated based on the volume density and theoretical density. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.

[0085] (2) Select "GB16534-2009 Fine Ceramics Room Temperature Hardness Test Method" as the standard, use Vickers hardness tester to test, calculate the Vickers hardness of the sample, test each sample three times, take the average value after measurement, and record the results in Table 1.

[0086] (3) Select "GB / T39862-2021 Test of thermal conductivity of high thermal conductivity ceramics" and "GB / T22588-2008 Flash method for measurement of thermal diffusivity or thermal conductivity" as the standards, use a laser thermal conductivity meter (Germany) to test the room temperature thermal diffusivity of the sample, and use a differential scanning calorimeter to measure the specific heat capacity of the sample. The thermal conductivity (W / (m·K)) of the sample is calculated based on the thermal diffusivity, specific heat and volume density of the sample. Each sample is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.

[0087] Table 1 Test results of density, hardness and thermal conductivity of silicon carbide heat exchange tubes

[0088] Test results Relative density (%) Hardness (GPa) Thermal conductivity (W / (m·K)) Example 1 99.5 39.3 267 Example 2 99.6 39.5 272 Example 3 99.9 39.7 275 Example 4 99.1 38.6 262 Example 5 99.3 38.9 265 Example 6 98.4 37.6 254 Example 7 98.8 38.3 257 Example 8 98.6 38.1 253 Example 9 98.3 36.8 246 Example 10 98.2 36.7 245 Embodiment 11 98.2 36.5 241 Example 12 98.7 37.4 256 Example 13 98.4 37.5 249 Embodiment 14 98.9 37.8 253 Comparative Example 1 97.5 33.3 227

[0089] It can be seen from Table 1 that the relative density of Examples 1-3 is greater than 99.5%, the Vickers hardness is greater than 39.3 GPa, and the thermal conductivity is greater than 267 W / (m·K), which shows that the silicon carbide heat exchange tube prepared in the present application has good density, hardness and thermal conductivity.

[0090] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that the mass ratio of dimethyl dioctadecyl ammonium chloride, acrylamide and polyethylene imine in Example 4 is 0.1:1:0.5, and the mass ratio of dimethyl dioctadecyl ammonium chloride, acrylamide and polyethylene imine in Example 5 is 0.5:1:0.5. The relative density in Examples 4 and 5 is less than 99.3%, the Vickers hardness is less than 38.9 GPa, and the thermal conductivity is less than 265 W / (m·K). The relative density in Example 3 is 99.9%, and the Vickers hardness is The density, hardness and thermal conductivity of Examples 4 and 5 are all reduced compared with Example 3. This is because the mass ratio of dimethyldioctadecylammonium chloride, acrylamide and polyethyleneimine is not within the specified range. Too much or too little dimethyldioctadecylammonium chloride will affect the steric hindrance and electrostatic stabilization effect, the synergistic effect of modified polyacrylamide and acetic acid molecules will decrease, and the dispersibility of modified silicon carbide powder will decrease, thereby reducing the density, hardness and thermal conductivity.

[0091] As can be seen from Table 1, the only difference between Examples 6 and 7 and Example 3 is that the amount of silane coupling agent and modified polyacrylamide in Example 6 accounts for 0.2% of the total weight of the slurry, and the amount of silane coupling agent and modified polyacrylamide in Example 7 accounts for 2% of the total weight of the slurry. The relative density in Examples 6 and 7 is less than 98.8%, the Vickers hardness is less than 38.3 GPa, and the thermal conductivity is less than 257 W / (m·K). Compared with Example 3, the density, hardness and thermal conductivity of Examples 6 and 7 are all reduced; this is because the amount of silane coupling agent and modified polyacrylamide is not within the specified range. Too much or too little silane coupling agent and modified polyacrylamide will affect the dispersibility of the modified silicon carbide powder, and then affect the solid content and viscosity of the slurry, so that the density, hardness and thermal conductivity are all reduced.

[0092] As can be seen from Table 1, the only difference between Examples 8, 9, 10, and 11 and Example 3 is that: in Example 8, no silane coupling agent is added when preparing the modified silicon carbide powder, and the remainder is supplemented with modified polyacrylamide; in Example 9, no dimethyl dioctadecyl ammonium chloride is added when preparing the modified silicon carbide powder, and the remainder is supplemented with acrylamide; in Example 10, no polyethyleneimine is added when preparing the modified silicon carbide powder, and the remainder is supplemented with acrylamide; in Example 11, the pretreated silicon carbide ultrafine powder is replaced with silicon carbide ultrafine powder; the relative density in Examples 8, 9, 10, and 11 is less than 98.6%, the Vickers hardness is less than 38.1 GPa, and the thermal conductivity is less than 253 W / (m·K); compared with Example 3, the density, hardness, and thermal conductivity of Examples 8, 9, 10, and 11 are all reduced; This is because the synthetic components of the modified silicon carbide powder are destroyed. Failure to add silane coupling agent will reduce the active groups of the pretreated silicon carbide ultrafine powder, reduce the dispersibility of the powder, and reduce the grafting performance of the modified polyacrylamide. Without adding dimethyl dioctadecyl ammonium chloride, the dispersibility of the modified silicon carbide powder decreases, the viscosity of the slurry increases, and the uniformity of the slurry decreases. Without adding polyethyleneimine, the three-dimensional structure of the polymer is destroyed, the steric hindrance and electrostatic stabilization effects are weakened, and the synergistic effect with the acetic acid molecules decreases. Replacing the pretreated silicon carbide ultrafine powder with silicon carbide ultrafine powder, the silicon carbide ultrafine powder is prone to agglomeration in the silane coupling agent and its dispersibility decreases. These changes will affect the dispersion properties of the modified silicon carbide powder, and then affect the viscosity and uniformity of the slurry, resulting in a decrease in density, hardness and thermal conductivity.

[0093] It can be seen from Table 1 that the only difference between Example 12 and Example 3 is that in Example 12, tetramethylammonium hydroxide is replaced by sodium hydroxide, the relative density in Example 12 is less than 98.7%, the Vickers hardness is less than 37.4 GPa, and the thermal conductivity is less than 256 W / (m·K). Compared with Example 3, Example 12 has reduced density, hardness and thermal conductivity; this is because tetramethylammonium hydroxide is replaced by sodium hydroxide, and sodium hydroxide lacks synergistic effect with the dispersant, and the uniformity and stability of the slurry are reduced, thereby reducing the density, hardness and thermal conductivity.

[0094] It can be seen from Table 1 that the only difference between Examples 13 and 14 and Example 3 is that the vacuum stirring degassing treatment time in Example 13 is 5 minutes, the vacuum stirring degassing treatment time in Example 14 is 45 minutes, the relative density in Examples 13 and 14 is less than 98.9%, the Vickers hardness is less than 37.8 GPa, and the thermal conductivity is less than 253 W / (m·K). Compared with Example 3, the density, hardness and thermal conductivity of Examples 13 and 14 are reduced; this is because the degassing treatment time that is too short is not thorough, and the degassing time that is too long will cause part of the solvent to evaporate, affecting the viscosity and stability of the slurry, and then affecting the formation and performance of the green body, so that the density, hardness and thermal conductivity are reduced.

[0095] It can be seen from Table 1 that the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the modified silicon carbide powder is replaced with silicon carbide ultrafine powder, the relative density in Comparative Example 1 is 97.5%, the Vickers hardness is 33.3 GPa, and the thermal conductivity is 227 W / (m·K). Compared with Example 3, the density, hardness and thermal conductivity of Comparative Example 1 are significantly reduced; this is because the modified silicon carbide powder is replaced with silicon carbide ultrafine powder, the silicon carbide ultrafine powder lacks modification treatment, the dispersibility is reduced, it is easy to agglomerate and precipitate, the stability of the slurry is reduced, and the density, hardness and thermal conductivity are significantly reduced.

[0096] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing high-performance pressureless sintered silicon carbide by slip casting, characterized in that: The following steps are involved: The sintering aid, pH regulator, dispersant, binder and debonding agent are mixed and dispersed in deionized water, and stirred evenly to obtain a premixed solution; Adding modified silicon carbide powder to the premixed liquid under stirring conditions, and gradually increasing the stirring rate as the amount of modified silicon carbide powder added increases, to obtain a slurry; Degassing the slurry to obtain degassing slurry; The degassed slurry is poured into a plaster mold for molding, and the excess slurry is poured out. After the green body is initially dried and shrunk, it is demoulded to obtain a green body; heating and drying the green body to obtain a dried green body; The dried green body is subjected to a trimming treatment, and the treated green body is placed in a sintering furnace for sintering according to a sintering system to obtain a silicon carbide ceramic product; The slurry includes the following components in percentage by weight: 3-7% sintering aid, 2.5-6% pH adjuster, 2-5% dispersant, 2-4% binder, 0.5-2% debonding agent, 15-22% deionized water, and the remainder is modified silicon carbide powder; The modified silicon carbide powder comprises pretreated silicon carbide ultrafine powder, silane coupling agent and modified polyacrylamide, and the amount of the silane coupling agent and the modified polyacrylamide accounts for 0.5-1% of the total weight of the slurry; The pretreated silicon carbide ultrafine powder is prepared by the following steps: ultrasonically dispersing the silicon carbide ultrafine powder into a hydrochloric acid aqueous solution to obtain a silicon carbide dispersion liquid, stirring the silicon carbide dispersion liquid for reaction, centrifuging, washing, and drying to obtain preliminary treated silicon carbide; mixing and dispersing the preliminary treated silicon carbide and glacial acetic acid to obtain a pretreated dispersion liquid, heating the pretreated dispersion liquid for reaction, centrifuging, washing, and drying to obtain the pretreated silicon carbide ultrafine powder; The raw materials for preparing the modified polyacrylamide include dimethyl dioctadecyl ammonium chloride, acrylamide and polyethyleneimine; The mass ratio of dimethyl dioctadecyl ammonium chloride, acrylamide and polyethylene imine is (0.2-0.4):1:0.5; The sintering aid includes carbon black and boron carbide; The pH adjuster includes tetramethylammonium hydroxide; The degassing treatment is a vacuum stirring degassing treatment, and the treatment time is 10-30 minutes; The sintering system includes the following contents: a heating rate of 8-12°C / min, keeping at 1150°C, 1330°C and 1550°C for 0.5-1.5h respectively, and a final sintering temperature of 2150-2250°C, keeping at 1.5-2.5h.